2016
DOI: 10.1111/sode.12179
|View full text |Cite
|
Sign up to set email alerts
|

Observed Emotions as Predictors of Quality of Kindergartners’ Social Relationships

Abstract: This study evaluated whether positive and anger emotional frequency (the proportion of instances an emotion was observed) and intensity (the strength of an emotion when it was observed) uniquely predicted social relationships among kindergarteners (N = 301). Emotions were observed as naturally occurring at school in the fall term and multiple reporters (peers and teachers) provided information on quality of relationships with children in the spring term. In structural equation models, positive emotion frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 64 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Prior studies have found that cortisol is associated with emotion regulation during early childhood (e.g., Fortunato et al, 2008;Miller et al, 2017). Prior research, however, has relied on examining emotion regulation using parent-reported measures (e.g., Bocknek et al, 2018;Caiozzo et al, 2018;Miller et al, 2017) or observational methods that focus on either positive or negative affect rather than the balance of positive and negative emotional expressions (Binder et al, 2020;Hernández et al, 2018;Hernández et al, 2017). In previous work that examined cortisol as a moderator of the relationship between family routines and emotion regulation (Miller et al, 2017), emotion regulation was assessed using parent report and defined as the overall intensity of the child's negative emotions and the child's typical ability to exhibit empathy as well as use words to express emotions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have found that cortisol is associated with emotion regulation during early childhood (e.g., Fortunato et al, 2008;Miller et al, 2017). Prior research, however, has relied on examining emotion regulation using parent-reported measures (e.g., Bocknek et al, 2018;Caiozzo et al, 2018;Miller et al, 2017) or observational methods that focus on either positive or negative affect rather than the balance of positive and negative emotional expressions (Binder et al, 2020;Hernández et al, 2018;Hernández et al, 2017). In previous work that examined cortisol as a moderator of the relationship between family routines and emotion regulation (Miller et al, 2017), emotion regulation was assessed using parent report and defined as the overall intensity of the child's negative emotions and the child's typical ability to exhibit empathy as well as use words to express emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity for emotion regulation is a critical developmental achievement of early childhood (Brophy-Herb et al, 2013;Hernández et al, 2017;Kwon et al, 2017) that has both biological and behavioral substrates that are influenced by social context and developmental stage (Perry & Calkins, 2018;Wagner et al, 2019). As children spend most of their time with family during early childhood, it is unsurprising that the family environment influences a child's emotion regulation during this developmental period, which is increasingly important as children face stressors when away from their parents (Eisenberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research assistants were trained to observe and rate child interactions in pre-coded videos (except during the first year of the first cohort) and pilot preschool settings based on prior methods that have demonstrated adequate reliability and predictive validity (e.g., Spinrad et al, 2004). Participants were observed in school by two or three research assistants, two to three times each week for nine to twelve weeks each semester (see Hernández et al, 2017, for more details). Research assistants had a pictorial list of participants for each classroom and coded individual children's emotional expressivity after a 30-s observation period.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, unregulated anger has been associated with aggression (Lochman, Barry, Powell, & Young, 2010). Moreover, negative emotion expression has been positively associated with peer difficulties in childhood (from age three to 16.5 in the following meta-analysis: Dougherty, 2006) and teacher-student conflict in kindergarten (Hernández et al, 2017) , suggesting that negative emotion is predictive of behavioral problems at school and resultant psychological maladjustment (Bukowski & Adams, 2005). Although positive emotional expressivity has been generally negatively associated with externalizing symptoms (e.g., Ghassabian et al, 2014;Olino et al, 2011;Shin et al, 2011), some research suggests that high intensity positive expressivity (e.g., exuberance) is associated with lower self-regulation and more externalizing behaviors in early childhood (Putnam, 2012;Stifter et al, 2008, from age two to 4.5).…”
Section: Behaviorsmentioning
confidence: 97%
“…As such, experiencing negative emotion, which would be expected to be reflected to some degree in individuals’ expression of emotion, may interfere with children’s cognitive and working memory task performance at school. Furthermore, increases in negative emotions and their expression may further impair children’s daily and cumulative learning across time through their effect on quality of children’s social interactions (Hernández, Eisenberg, Valiente, Spinrad, et al, 2017; Hernández et al, 2016).…”
Section: The Relation Of Emotional Expressivity To Academic Outcomes:...mentioning
confidence: 99%